(untitled) (World Bulletin of Public Health, 2025)
The article presents the results of a study of the external respiratory system and cardiovascular system in adolescents living in the Republic of Uzbekistan. It was found that adolescents have some excess of the level of indicators in the functioning of the adaptive respiratory system.